Screening of bacteriocinogenic lactic acid bacteria and their characterization as potential probiotics - Pinto, Ana (2020)
Probiotics are living microorganisms used as nutritional additives that confer health benefits on the host. Their use in food products is very attractive, especially if they could also inhibit important foodborne athogens. In this study, antimicrobial activity against several foodborne pathogens was screened for 280 lactic acid bacteria (LAB) isolated from di erent food products and the probiotic characteristics of bacteriocinogenic isolates were evaluated. Seven out of 280 LAB isolates were selected due to their bacteriocinogenic properties and identified by 16S rRNA gene sequence analysis as Pediococcus pentosaceus (n = 6) and Lactobacillus plantarum (n = 1). Virulence factors and antibiotic resistances were not detected for any of the isolates. Except for L. plantarum R23, all the isolates were able to survive through the simulated gastrointestinal tract conditions. Only P. pentosaceus CFF4 was able to adhere to Caco-2 cells after the simulated gastrointestinal tract passage. In conclusion, even though in vivo studies should be performed, P. pentosaceus CFF4, which was also able to inhibit the growth of foodborne pathogens in vitro, seems to be a potential probiotic to be used in the food industry.